Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Make A Match Terhadap Kemampuan Pemahaman Konsep Matematis Dan Motivasi Belajar Peserta Didik Kelas VIII SMPN 3 Padang Panjang - FITRI FEBRIANI (Jurnal Edukasi dan Penelitian Matematika, 2019)
Understanding concepts ability and learning motivation is one of the important aspects in learning. Based on the results of observations and preliminary tests that have been carried out, it appears that the understanding of mathematical concepts and learning motivation of students in class VIII of SMPN 3 Padang Panjang is still low. One effort that can be done is to apply the Make A Match Learning Model. This type of research is a combination of quasi-experimental and descriptive research. The study design was a randomized control group only design and one group pretest-posttest design. The study population was all VIII grade students of SMPN 3 Padang Panjang with sample of grades VIII.E and VIII.F. The results showed that the ability to understand the mathematical concepts of students who use the Make A Match Learning Model is better than of students who learn by using the Direct Learning Model.Keywords - Understanding Of Mathematical Concepts, Make A Match, Direct Learning,  Motivation Learning.